The relations among measures of performance on fixed-interval schedules - Gollub, Lewis R. (1964)
Quantitative measures of the performances of seven rats and two pigeons under FI schedules of reinforcement were obtained. For the rats (under FI 2 and FI 100 sec) the mean response rate and two measures of the temporal distribution of responses within the interval (quarter-life and an Index of Curvature) were computed for individual intervals. The measures of curvature were highly correlated with each other, whereas the response rate was only moderately correlated with either of them. Similar results were found for comparisons of the same measures on a session-by-session basis. The performances of the pigeons (under FI 10) were analyzed to yield response rate, quarter-life and elapsed time to the first, fifth and tenth response. Response rate was only moderately correlated with quarter-life, whereas quarter-life and time to the fifth or tenth response were highly correlated. Measures of temporal distribution based on an average of the intervals of a daily session were highly similar to the means of those measures calculated from the individual intervals.